Decreasing ventricular infections through the use of a ventriculostomy placement bundle: Experience at a single institution - (:unkn) unknown (My University, 2013)
Object. Ventricular infection after ventriculostomy placement carries a high mortality rate. Responding to ventriculostomy infection rates, a multidisciplinary performance improvement team was formed, a comprehensive protocol for ventriculostomy placement was developed, and the efficacy was evaluated. Methods. A best-practice protocol was developed, including hand hygiene before the procedure; prophylactic antibiotics; sterile gloves changed between preparation, draping, and procedure; hair removal by clipping for dressing adherence; skin preparation using iodine povacrylex (0.7% available iodine) and isopropyl alcohol (74%); full body and head drape; full surgical attire for the surgeon and other bedside providers; and an antimicrobial- impregnated catheter. A checklist of critical components was used to confirm proper insertion and to monitor practice. Procedurespecific infection rates were calculated using the number of infections divided by the number of patients in whom an external ventricular drainage (EVD) device was inserted × 100 (%). Data were reported back to providers and to the committee. Bundle compliance was monitored over a 4-year period. Results. At the authors' institution, 2928 ventriculostomies were performed between the beginning of the fourth quarter of 2006 and the end of the first quarter of 2012. Although the best-evidence bundle was applied to all patients, only 588 (20.1%) were checklist monitored (increasing from 7% to 23% over the study period). The infection rate for the 2 quarters before bundle implementation was 9.2%. During the study period, the rate decreased quarterly to 2.6% and then to 0%. Over a 4-year period, the rate was 1.06% (2007), 0.66% (2008), 0.15% (2009), and 0.34% (2010); it was 0% in 2011 and the first quarter of 2012. The overall EVD infection rate was 0.46% after bundle implementation. Conclusions. Bundle implementation including an antimicrobial-impregnated catheter dramatically decreased EVD-related infections. Training and situational awareness of appropriate practice, assisted by the checklist, plus use of the antibiotic-impregnated catheter resulted in sustained reduction in ventriculitis. © AANS, 2013.
Keywords: Care bundle; Central nervous system infection; Diagnostic and operative techniques; Percutaneous surgery; Quality improvement; Ventricular drainage